Navigating treacherous waters: Exploring the dual career experiences of European Research Council applicants - Schels, Brigitte; Connolly, Sara; Fuchs, Stefan; Herschberg, Channah; Vmkenburg, Claartje J. (Nomos Verlagsgesellschaft mbH und Co KG, 2023)
Careers of scientists do not unfold in a social vacuum. According to the concept of linked lives (Moen, 2003), the career of one partner has implications for the career of the other. Using a quantitative survey and qualitative interviews we explore the experiences of navigating dual careers for a sample of scientists who applied for a European Research Council (ERC) grant. While the notion of an ideal scientist is built on an individualistic model of unrestricted international mobility and dedication, our quantitative analysis shows that the majority of ERC applicants have an employed partner, who is often also a scientist, and children. The majority of ERC applicants with an employed partner say both careers are equally important, but the proportion is higher among women ERC applicants. These scientists experience difficulties in coordinating and combining dual careers, even if their own career is considered more important. This is evident for established scientists as well as for scientists who are in the 'rush hour of life. From the scientists' lived experiences it becomes evident that the ERC applicants want to comply with the notion of the 'ideal' scientist but face limitations, especially when mobility opportunities are constrained by the portability of the partners' careers. Dual-career cycling dilemmas are raised by mobility events, often resulting in priority shifts through a competing rather than synchronic process. These dilemmas arise for both men and women scientists, but some of the consequences-where and with whom the children live and who has primary care responsibilities-are quite gendered. We conclude with recommendations for employers and funders in supporting dual careers in science.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Academic couples; Dual career couples; Europe; International mobility; Linked lives; Scientific career paths